PROTECTION OF THE RIGHTS OF HEIRS TO THE DIGITAL ASSETS OF THE DECEASED IN THE INDONESIAN CIVIL INHERITANCE SYSTEM WITH A COMPARATIVE APPROACH TO RUFADAA - Aprilianto Mardiansyah; Mahfud Fahrazi; Trinas Dewi Hariyana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The development of the digital economy has given rise to a new form of wealth in the form of digital assets that challenge the classic paradigm of civil inheritance law, which is based on physical possession. This study aims to analyze the position of digital assets in the Indonesian civil inheritance law system and formulate an effective and adaptive legal protection model for heirs. This research is a normative legal study using a legislative, conceptual, and comparative legal approach. The results of the study show that through a systematic interpretation of Articles 499, 830, and 833 of the Civil Code, digital assets can be classified as intangible property rights that are included in the estate as long as they meet the criteria of economic rights (vermogensrechten). However, legal protection is still declarative due to the separation between legal ownership and technical control by digital platform operators. Therefore, this study formulates an integrative protection model that includes normative legitimacy, restrictions on inheritance objects, mechanisms for settling digital passiva, and administrative supervision of electronic system operators. This model is expected to bridge inheritance law norms with the technical realities of the digital ecosystem in a proportional and operational manner.